2019
DOI: 10.18632/aging.101756
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of immune checkpoint molecules in head and neck cancer: a meta-analysis

Abstract: Immune checkpoint molecules are important targets in cancer immunotherapy, but their association with prognosis in patients with head and neck cancer is controversial. In this meta-analysis, we searched for 12 immune checkpoint molecules in the PubMed, Embase and Cochrane Library databases and retrieved 52 studies with 7127 participants. Among the molecules included in the search, indoleamine 2, 3-dioxygenase (IDO), programmed death ligand 1 (PD-L1), and programmed death 1 (PD-1) met the inclusion criteria for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 86 publications
2
13
5
Order By: Relevance
“…The results of another recently published meta-analysis elucidating the prognostic value of some immune checkpoints in head and neck cancer were completely different from our meta-analysis and the previous study of head and neck that we just mentioned above [45]. The analysis demonstrated that PD-L1 expression higher indicated better OS in HNC, especially in NPC (p = 0.01).…”
Section: Discussioncontrasting
confidence: 99%
“…The results of another recently published meta-analysis elucidating the prognostic value of some immune checkpoints in head and neck cancer were completely different from our meta-analysis and the previous study of head and neck that we just mentioned above [45]. The analysis demonstrated that PD-L1 expression higher indicated better OS in HNC, especially in NPC (p = 0.01).…”
Section: Discussioncontrasting
confidence: 99%
“…The PD-L1 expression level is an acknowledged prognostic factor in different cancers. 53 55 PD-L1 expression in tumor cells is a confirmative biomarker for predicting response to PD-1/PD-L1 checkpoint inhibition according to the analyses of more than 10 different solid tumors, which was the same as that for breast cancer in our results. 56 58 PD-L1 mainly expresses on tumor-infiltrating immune cells rather than on tumor cells in patients with TNBC, thus it might be a prognostic factor for response.…”
Section: Discussionsupporting
confidence: 73%
“…In the second publication, Jia et al examined the prognostic value of indoleamine-2,3-dioxygenase, PD-L1, and programmed death 1 (PD-1) in patients with head and neck cancer. 20 The authors found that patients with NPC and higher levels of PD-L1 expression had a better OS, which is not in agreement with our study. This result was associated with no heterogeneity and remained statistically significant after performing a sensitivity analysis by study quality.…”
Section: Prognostic Role Of Pd-l1 In Npccontrasting
confidence: 87%